Determinant of Taxpayer Compliance Among SMEs During Covid-19 Pandemic - Hidayatulah, Arif (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to determine the effect of taxpayer knowledge, tax awareness, and tax incentives on MSME taxpayer compliance during the covid-19 pandemic in Kampar. This quantitative research uses data obtained through a questionnaire survey distributed to MSME taxpayers who are registered at KPP Pratama Bangkinang. A total of 100 samples were obtained and further processed. Data were analyzed using multiple regression to test the hypothesis. The results show that MSME taxpayer compliance in Bangkinang is strongly influenced by taxpayer knowledge, that tax knowledge is something that is known to humans about taxation, both taxpayers, tax benefits, tax rates, tax sanctions, and so on. Taxpayer awareness is formed by the dimensions of the taxpayer's perception, knowledge of the taxpayer, characteristics of the taxpayer, and tax counseling. Tax incentives are proven to affect taxpayer compliance